2016
DOI: 10.2147/ott.s110235
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of angiosarcoma of the scalp with apatinib: a case report

Abstract: Angiosarcoma is a rare and aggressive vascular malignancy with a poor prognosis. There is no standard chemotherapy regime for advanced angiosarcoma. Here, we report a case of advanced angiosarcoma that was successfully treated with apatinib, an oral tyrosine kinase inhibitor targeting the intracellular domain of vascular endothelial growth factor receptor-2 (VEGFR-2). To our knowledge, this is the first case to report the successful use of apatinib for angiosarcoma. Furthermore, the administration of apatinib … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 10 publications
3
22
0
Order By: Relevance
“…7 A case of 74-y-old angiosarcoma patient was confirmed with local tumor recurrence with multiple metastases. 8 His PFS time was as long as 12 months. An 18-y-old alveolar soft part sarcoma case with multiple lung metastases achieved a PR and a PFS of 12 months after Figure 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 A case of 74-y-old angiosarcoma patient was confirmed with local tumor recurrence with multiple metastases. 8 His PFS time was as long as 12 months. An 18-y-old alveolar soft part sarcoma case with multiple lung metastases achieved a PR and a PFS of 12 months after Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…Promising efficacy of apatinib was reported in several subtypes of sarcomas. [6][7][8][9][10] We further retrospectively investigated the outcomes of apatinib in 31 patients with advanced metastatic or recurrent sarcoma who pretreated with at least one chemotherapy regimen or refused to receive chemotherapy. in 7 patients (22.6%) and trunk in 3 patients (9.7%).…”
Section: Introductionmentioning
confidence: 99%
“…Angiosarcoma is a rare aggressive malignant tumor of vascular endothelial cells, the face and scalp regions account for more than 50% of cutaneous angiosarcomas. Surgery could be the most effective method of treatment, but for advanced and metastatic angiosarcoma, chemotherapy would be the main choice . However, adjuvant postoperative radiotherapy improves the outcome …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that positive immunohistochemical staining for VEGF occurs in 14% of primary angiosarcomas and of its 3 known receptors, VEGFR3 has been shown to be present in 50% of all angiosarcomas (5). Given the potential involvement of these signalling pathways in the pathogenesis of post-radiotherapy angiosarcoma, it seems reasonable to consider the use of VEGF antagonists such as bevacizumab (humanized monoclonal antibody targeting VEGF-A), sorafenib (an inhibitor of VEGFR1, VEGFR2, VEGRF3 among other receptors) (15), pazopanib (an inhibitor of VEGF2 and VEGF3) (16,17), apatinib (an inhibitor of VEGF2) (18) or even thalidomide (known to suppress VEGF) (19) in the treatment of angiosarcoma.…”
Section: Discussionmentioning
confidence: 99%